Peranan Lembaga Swadaya Masyarakat SPEK-HAM Surakarta dalam memberikan layanan bantuan hukum pada Perempuan korban kekerasan seksual - Kartika, Ringgit Benazir; Rejekiningsih, Triana; Yuliandari, Erna (Academy of Education Journal, 2024)
This research aims to determine: (1) The role of the non-governmental organization SPEK-HAM Surakarta in providing legal aid services to women victims of sexual violence, (2) The obstacles faced by the non-governmental organization SPEK-HAM Surakarta in providing legal aid services to women victims of sexual violence. This study used qualitative research methods. In this research, the results were obtained in the form of: (1) The role of the Non-Governmental Organization SPEK-HAM Surakarta in providing legal aid services to women victims of sexual violence, namely (1) Receiving SPEK-HAM Case Complaint Reports; (2) Approach to Victims and Legal Consultation; (3) Mediation; (4) Legal Assistance. 2) The obstacles experienced are (1) During the mediation process, if the case is continued to the realm of law, the victim's family is also involved in the case, overcome by mediation accompanied by compensation, (2) the lack of perspective from the Police towards women victims of sexual violence is overcome by providing education and understanding for the police so they can handle cases of sexual violence based on the victim's perspective.